A histology-based study in apparently healthy wild freshwater stingrays Potamotrygon motoro - de Moraes, Julieta Engrácia [UNESP] (2016)
Histopathological studies are important as a reference in pathological process. There are a few of these studies in elasmobranchs. The aim of this study was to describe the histology of kidney, spleen, liver, and gills of wild apparently healthy Potamotrygon motoro. However, we observed some pathological findings in these animals. Nineteen P. motoro were collected from the Parana River, Brazil. Histology of kidney, spleen, liver, and gills were performed according to usual procedures. Briefly, the organs were immersed in 10 % formaldehyde solution for 48 h and routinely processed, embedded in paraffin (5–6 mm thick), and subsequent staining with hematoxylin–eosin (HE), Perls’, and Schmorl’s stains. Histological surface areas were measured using Image Pro Plus software 6.3. We observed that melanomacrophages around the portal vein were larger and more abundant than in the area without the bile duct. Moderate steatosis was observed in most fish, large amount of melanomacrophages and lymphocytes in the gills, liver, and spleen comparing with other studies in this species that could suggest that the immune system in these animals is constantly active. No clinical signs were observed in the fish. Studies are necessary to characterize the immune response against pathogens in elasmobranchs, especially in the Potamotrygon species.